PENGARUH PERMAINAN TRADISIONAL TERHADAP HASIL BELAJAR ATLETIK NOMOR LARI JARAK PENDEK 100 METER SISWA KELAS VII DI SMP NEGERI 2 TELUKJAMBE BARAT - Septa Rafael Telaumbanua; Rekha Ratri Julianti; Abdul Salam Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to improve short-distance running learning outcomes using traditional games. This study uses a quantitative approach with this research method is a pre-experimental design study using One-Group Pretest- posttest design. This study was conducted at SMP Negeri 2 Telukjambe Barat. The population of this study were students of class VII of SMP Negeri 2 Telukjambe Barat. The sample in this study was taken using the cluster random sampling technique, the sample was students of class VII-A of SMP Negeri 2 Telukjambe Barat. The research instruments include cognitive, affective and skills. To determine the effect of traditional games on learning outcomes of 100-meter short-distance running, data analysis to see the effect using hypothesis testing. The results of this study are an average pretest of 156.82 and a posttest of 264.69. The results of the paired sample test analysis with the data obtained from this study are an increased value (2-tailed) = 0.000 less than the increased level (α) = 0.05, so H0 is rejected and H1 is accepted. It can be concluded that traditional games can have an effect on improving the learning outcomes of 100- meter short-distance running for grade VII students at SMP Negeri 2 Telukjambe Barat.